2021
DOI: 10.3390/diagnostics11040626
|View full text |Cite
|
Sign up to set email alerts
|

Can the Determination of HE4 and CA125 Markers Affect the Treatment of Patients with Endometrial Cancer?

Abstract: The aim of our research was to determine the use of CA125 and HE4 as prognostic factors in patients with different clinical staging of endometrial cancer. Sixty-two patients with advanced endometrial cancer and 287 patients with early stage endometrial cancer participated in the study. Based on the results obtained in the study, the cut-off value for HE4 was established at 186 pmol/l and correlated with the possibility of cytoreductive surgery in patients with recurrent endometrial cancer. Univariate logistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…The flow chart of literature screening is shown in Figure 1. among these studies, eight were from China, [7][8][9][10][11][12][13][14] four from Italy, [15][16][17][18] four from Poland, [19][20][21][22] three from Iran, [23][24][25] two from Australia, 26,27 two from Czech Republic, 28,29 two from Egypt, 30,31 two from Thailand, 32,33 two from The Netherlands, 34,35 two from Turkey, 36,37 and one each was from America, Austria, Denmark, India, Ireland, Slovenia, and Spain. [38][39][40][41][42][43][44] Thirty-three studies described the relationship between serum HE4 levels and the clinicopathological characteristics of EC, three studies described the relationship between tissue HE4 expression and the clinicopathological characteristics of EC, and two studies examined HE4 expression in both samples.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…The flow chart of literature screening is shown in Figure 1. among these studies, eight were from China, [7][8][9][10][11][12][13][14] four from Italy, [15][16][17][18] four from Poland, [19][20][21][22] three from Iran, [23][24][25] two from Australia, 26,27 two from Czech Republic, 28,29 two from Egypt, 30,31 two from Thailand, 32,33 two from The Netherlands, 34,35 two from Turkey, 36,37 and one each was from America, Austria, Denmark, India, Ireland, Slovenia, and Spain. [38][39][40][41][42][43][44] Thirty-three studies described the relationship between serum HE4 levels and the clinicopathological characteristics of EC, three studies described the relationship between tissue HE4 expression and the clinicopathological characteristics of EC, and two studies examined HE4 expression in both samples.…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Insin et al showed that three-year OS was poorer (71% vs. 96%) in patients with pre-operative serum HE4 ≥ 70 pM who had surgery [80]. Cymbaluk-Ploska et al also showed that baseline serum HE4 < 70 pM correlated with better OS and DFS [81].…”
Section: He4 As a Prognostic Markermentioning
confidence: 99%
“…Many clinical studies have shown that deciding whether to conduct radiotherapy or chemotherapy according to the risk of tumors can not only avoid unnecessary pain and economic burden brought by overtreatment of early-stage patients, but also avoid undertreatment of high-risk tumors, delay recurrence and improve the quality of life ( 2 4 ). Previous studies have proposed predicting the myometrial invasion and clinical outcome of EC by combining clinical and pathological indicators ( 5 , 6 ). Tumor size, myometrial invasion, lymph vascular space invasion (LVSI) and other parameters obtained by postoperative tumor pathology can certainly be used to evaluate the EC prognosis.…”
Section: Introductionmentioning
confidence: 99%